PENGENDALIAN DAN PERBAIKAN KUALITAS PRODUK FURNITURE DENGAN PENERAPAN METODE SQC (STATISTICAL QUALITY CONTROL) DAN FTA (FAULT TREE ANALYSIS) - Ari Pranata Primisa Purba; Rizki Fadhillah Lubis; Tosty Maylangi Sitorus (Jurnal Sains dan Teknologi: Jurnal Keilmuan dan Aplikasi Teknologi Industri, 2022)
CV. XYZ is a company engaged in the production of wood into finished goods (furniture), one of which is wooden chairs. In the process of making wooden chairs, various types of damaged products such as broken, painted (varnished), scuffed, and loose are still found. This study aims to analyze the quality control of CV. XYZ and provide suggestions for improvement to reduce product defects, using the Statistical Quality Control (SQC) method with seven tools and the Fault Tree Analysis (FTA) method. The results show that in the period January 2021-February 2022 the average percentage of defective products per month is 5.63%, where this result exceeds the company's standard of 5%. The results of the analysis stated that abrasion defects and stretching defects dominated the overall defective products, with the causal factors being the lack of supervision during the production process and no routine machine maintenance schedule being carried out. The suggested improvement given is to appoint a senior worker as a supervisor at each work station, hold a briefing before and after production is completed by the management to all operators, then make a special schedule for periodic inspection, maintenance, and repair of machines and equipment at the workplace. outside the production schedule, and the last is to create and place work instructions on the use and maintenance of the machine.